RESILIENSI PENGUATAN KETAHANAN PANGAN DAERAH DI INDONESIA - amin Lombok Lombok; Lalu Budiman; Dedi Suhendi (IPDN Kampus NTB, 2024)
Food security is increasingly important for regions facing climate variability, economic instability, and social disparities. Regional food security refers to the ability of a region to consistently meet food needs amidst external stresses and shocks. This study examines the factors influencing food security in a specific region, aiming to understand local challenges and strategies that underpin food access and production. The study used a qualitative approach, collecting data through interviews with local farmers, community leaders, and government officials. In-depth interviews and focus group discussions provided insights into local perceptions of food security, adaptation mechanisms, and external influences on agricultural productivity. The findings revealed that food security in the region is closely linked to agricultural stability, water resource availability, and institutional support. Key challenges include market price volatility, limited access to modern agricultural technologies, and environmental pressures. However, traditional knowledge, community solidarity, and adaptive practices have strengthened resilience. Collective actions, such as community-based resource management and cooperative farming, were highlighted as significant in overcoming resource constraints and maintaining food security.